Laser Nanosecond Technique, FTIR and AFM Application to Find Physical Properties of PVA Doped with Dye - Wasan Ali Khudhair; Narjis Zamil Abdulzahra (New Trends in Physical Science Research Vol. 7, 2022)
In this work, polyvinyl alcohol (PVA) is prepare by casting technique, it is doped with different weights of Methyl blue (MB). Fourier transforms infrared spectroscopy (FTIR) analysis shows the peaks become intensity and shifting wave number. Atomic force microscopy images show decreasing in grain size from 141.72 to 72.32 nm, the measured Hardness by an alternate new method using laser spot calculations shows increased harness about 7 times from (29 to 202) N/cm2 .